2016
DOI: 10.3109/1354750x.2016.1160289
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin corrects ERK pathway hyperactivation in fragile X syndrome: potential of platelet’s signaling cascades as new outcome measures in clinical trials

Abstract: Platelets' signaling pathways provide biomarkers that can be used as treatment outcome measures in FXS clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 102 publications
3
35
1
2
Order By: Relevance
“…FMRP binds and acts as a repressor of translation of a number of mRNAs including those involved in the ERK cascade signaling pathway [74]; thus, the lack of this negative translational control is believed to lead to upregulation of these pathways and consequently to the altered synaptogenesis observed in FXS. Several studies have shown upregulation of ERK in both mouse and human (reviewed in [75]), who, contrary to our observations, recently reported a reduction of the ERK pathway signaling following a lovastatin treatment. Specifically, they reported 1.6-fold increase in basal ERK phosphorylation levels in blood platelets derived from subjects with FXS, which was rescued by lovastatin treatment and correlated with clinical response.…”
Section: Biomarkers Of Lovastatin-induced Changecontrasting
confidence: 99%
“…FMRP binds and acts as a repressor of translation of a number of mRNAs including those involved in the ERK cascade signaling pathway [74]; thus, the lack of this negative translational control is believed to lead to upregulation of these pathways and consequently to the altered synaptogenesis observed in FXS. Several studies have shown upregulation of ERK in both mouse and human (reviewed in [75]), who, contrary to our observations, recently reported a reduction of the ERK pathway signaling following a lovastatin treatment. Specifically, they reported 1.6-fold increase in basal ERK phosphorylation levels in blood platelets derived from subjects with FXS, which was rescued by lovastatin treatment and correlated with clinical response.…”
Section: Biomarkers Of Lovastatin-induced Changecontrasting
confidence: 99%
“…Remarkably, several targets of FMRP belong to the two major mGluR-signaling cascades controlling the expression of related proteins, the ERK 11 - and the mTOR 12 - pathway: ERK, PI3K 13 , PIKE 14 , GSK3 15 and mTOR are target mRNAs of FMRP (Darnell et al, 2011 ; Ascano et al, 2012 ). Both signaling pathways turned out to be exaggerated not only in the hippocampus of Fmr1 −/y mice (ERK pathway: Hou et al, 2006 ; Michalon et al, 2012 ; mTOR pathway: Sharma et al, 2010 ; Liu Z. H. et al, 2012 ; Bhattacharya et al, 2016 ; Choi et al, 2016 ), but also in humans (Weng et al, 2008 ; Hoeffer et al, 2012 ; Wang X. et al, 2012 ; Kumari et al, 2014 ; Pellerin et al, 2016 ).…”
Section: The Fragile X Syndrome — Of Micementioning
confidence: 99%
“…In fact, some data even suggest that mTOR inhibition with Rapamycin might cause neurodegeneration (Lin et al, 2013 ). The hopes are therefore now on clinical trials with Lovastatin (Caku et al, 2014 ; Pellerin et al, 2016 ) and Metformin (Dy et al, 2018 ).…”
Section: The Fragile X Syndrome — Of Micementioning
confidence: 99%
“…Additionally, studies using the Fmr1 -/y rat model show that lovastatin treatment at a juvenile age can prevent the emergence of complex cognitive phenotypes [21]. Based on the positive outcome with lovastatin in Fmr1 -/y animal models, two open-label clinical trials tested the viability of lovastatin for the treatment of FX [22,23]. Both studies revealed a significant improvement with lovastatin treatment, and a double-blind placebocontrolled trial is ongoing [6].Interestingly, the availability of lovastatin is not widespread in Europe and is not licensed for use in the UK.…”
mentioning
confidence: 99%